Flat sheet thin film composite forward osmosis membranes for water treatment and purification: A review on modification techniques and concepts - Almansouri, Hamza E.; Edokali, Mohamed; Mazrul Nizam, Abu Seman (Taylor & Francis, 2024)
Forward osmosis (FO) is an extensively studied osmotic process primarily used in wastewater treatment and purification. It has recently gained recognition as a highly promising membrane technology due to its simplicity, low energy consumption, and minimal fouling compared to pressure-driven membrane technologies. However, the application of the FO process faces challenges such as concentration polarization, reverse solute diffusion, and fouling. Enhancing FO performance requires an efficient membrane that offers high water flux, low solute flux, reduced fouling, and controlled concentration polarization. Among the most effective membranes are polyamide thin-film composite (PA-TFC) membranes, which are created through interfacial polymerization (IP) on porous supports and are mostly used in water treatment and desalination. Currently, there is a need to develop innovative FO membranes that achieve a fine balance between water permeability and solute rejection in the top layer. Additionally, the support layer must be designed to ensure high permeate flow. This paper reviews recent advancements in PA-TFC FO membrane processes and fabrication techniques aimed at modifying the top active layer and support layer, along with other modifications such as interlayered and double-skinned membranes. Finally, further research is required to investigate the scalability of these modification techniques for practical applications.